The impact of oil price shocks on stock exchanges in Caspian Basin countries - Kose, Nezir; Unal, Emre (Pergamon-Elsevier Science Ltd, 2020)
In this work, the impact of oil price shocks on the stock exchanges of three countries in the Caspian Basin - Iran, Kazakhstan and Russia - was examined through a structural vector autoregression (SVAR) model. For the research, monthly data from the stock exchanges, the oil price, inflation, industrial production and exchange rates were collected between March 2005 and June 2018. According to the results of variance decomposition, in these three countries, the impact of negative oil price shocks on the stock exchanges was stronger than that of positive shocks, and constituted the largest source of changes in the three stock exchanges. In addition, according to the results of impulse response functions, the response of the stock exchanges in the three countries to negative oil shocks was highly significant. Consequently, these countries should avoid macroeconomic imbalances and falls in their stock exchanges due to the negative impact of the oil price, and should instead focus on industrial production that will contribute to exports. In this way, they can avoid the negative impact of oil price shocks on their stock exchanges. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Caspian basin; Oil price shocks; Stock exchanges; Structural VAR